Optical detection of plasmonic and interband excitations in 1-nm-wide indium atomic wires - Hoang, Chung-Vu; Kubber, C. J.; Han, G.; Rigamonti, S.; Sanchez-Portal, D.; Enders, D.; Pucci, A.; Nagao, T. (Applied physics letters, 2010)
Infrared spectroscopy is demonstrated to sensitively detect electronic excitations in 1-nm-wide wires made of indium. The polarization-dependent spectra measured at room temperature show a strong broadband plasmonic absorption feature in the direction parallel to the wires, while in the perpendicular direction the wires stay nearly transparent in the same spectral range. At 88 K the wires do not show this broadband absorption anymore, but instead, several interband-transition features arise for both polarizations, in agreement to the gap opening of the metal-to-insulator transition as known for this one-dimensional structure.